Syariah Dan Negara Ragam Prespektif dan Implementasi di Asia Tenggara - M. Zaki, Dian Mustika (Pustaka Pelajar & syariah Press, 2015)
Syariah Dan Negara Ragam Prespektif dan Implementasi di Asia Tenggara